PENGARUH PERTUMBUHAN LABA DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA DENGAN MEDIASI PERENCANAAN PAJAK PADA JAKARTA ISLAMIC INDEX - Muhammad Sapruwan; Vina Marlisa (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to obtain empirical evidence regarding the effect of earnings growth and firm size on earnings quality through mediation of tax planning in Islamic companies listed on the Jakarta Islamic Index (JII). Data processing was obtained from twelve sharia companies consistently listing in the Jakarta Islamic Index (JII) during the 2017-2021 period through purposive sampling method and analyzed using a structural model with the help of the WrapPLS software version 5. The findings of the study show that tax planning is proven to mediate the effect of growth earnings and company size on earnings quality. Directly, profitability and firm size have no effect on earnings quality. Tax planning directly has a positive effect on earnings quality. Profitability mediated by tax planning has a negative effect on earnings quality, while firm size through tax planning has a positive effect on earnings quality.